MENGENAL PENTAKOSTALISME DI INDONESIA - Hendarto Supatra (Sekolah Tinggi Theologia Abdiel, 2019)
The author gives enough introduction of the development of the Pentecostal movement in the history of the Christian Church. The movement of the Pentecostalism was an unique development because the Holy Spirit is believed as the inisiator of the movement. Therefore, the Pentecostal churches really depends on the work of the Holy Spirit (without separated from the work of the work of God the Father and Jesus Christ). Furthermore, this article describes the development of the Pentacostal movement, especially in Indonesian context and observes the unique and positive things of the Pentacostalism, its doctrine and dangerous teachings, especially in Indonesian context. The author believes that Pentecostalism will be the face of Christianity in the future.